THE EVOLUTION OF SOCIETAL MARKETING IN SERVICE BUSINESSES: ORIGINS, TRANSFORMATIONS AND FUTURE PERSPECTIVES (1970-2023) - Bilalou Foundiku Montie (PEOPLE: International Journal of Social Sciences, 2025)
The aim of this article is to retrace the paradigm changes in the evolution of marketing theory through four periods that led to the emergence of societal marketing, as well as the causes behind these changes. Our work is based on an in-depth literature review and theoretical analysis founded on the work of P. Kotler and G. Zaltman (1971), which contributed to the reconceptualization of the concept of societal marketing. We then examine the factors that have favored the successful implementation of societal marketing in service companies, such as closer relationships with customers, win-win strategies for all, and a focus on relational trust. This analysis is inspired by the work of Grönroos (2007) on interactive service models, where transparent communication and customer experience reinforce consumer loyalty and commitment. Finally, we focus on future prospects that could completely revolutionize societal marketing and enable its consensual, gradual and widespread acceptance within service companies, which is not yet the case today. Despite notable advances, only a small minority of companies are implementing the principles of societal marketing. However, changing consumer behavior, the rise of artificial intelligence, increased competition and a growing number of brands for a limited demand, as well as existing regulations, have obliged many companies to prioritize customer loyalty strategies. These factors will increase the pressure on companies to meet societal marketing standards.